Integrated application for automatic schedule-based distribution and monitoring of irrigation by applying the waterfall model process - Aulia Naufal Afif; Fiftin Noviyanto; Sunardi Sunardi; Son Ali Akbar; Eko Aribowo (Institute of Advanced Engineering and Science, 2020)
40% of areas in Indonesia are still using rainwater as a source for irrigation. Type of wetland rainwater always depends on weather that is currently difficult to predict. In addition, the frequency of field cultivation became limited. Irrigation water can come from a dam or a spring in the mountains. Limited water source generates the need to manage water distribution in all areas of rice fields. For every 1 hectare fields, at least 0.5 litres of water per second is needed. The imbalance between the field and the available water discharge can cause conflicts in the Community farmers manage field. The purpose of this research is to assist in the Assembly Of Farmer Water users (